Hubungan Terpaan Hoax Covid-19, Kompetensi Komunikasi Juru Bicara Covid-19 Dan Tingkat Kepercayaan Masyarakat Pada Kinerja Pemerintah Pusat Dalam Menangani Covid-19 - Audrey Nathania Priscilla Karundeng; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
This study aims to determine the correlation between Covid-19 hoax exposure, the communication competence of the Covid-19 spokesperson, and the level of public trust in the performance of the central government in dealing with Covid-19. This research uses Mass Media Effect Theory and Source Credibility Theory. To determine the sample, this study uses a non-probability sampling technique. The number of samples that used in this study is 50 people, male/female, aged 35-50 years, domiciled in Bandar Lampung who actively accessed Covid-19 information and had watched the press conference of the Covid-19 spokesperson. The results showed that Covid-19 hoax exposure with the level of public trust in the performance of the central government has no correlation. Furthermore, the communication competence of the Covid-19 spokesperson with the level of public trust in the performance of the central government has a significant correlation.